Effect of interface stresses on anisotropic structure of the articular surface - Punantapong B. (2014)
Fatigue failure of anisotropic structure of the artificial articular has been implicated in a number of clinical failure scenarios, especially the fatigue behaviour of the articular surface is poorly understood, At the same time, there is no established design and procedure, which is applicable to all load-bearing implants. However, materials degradation significantly may also be increased the life of sample by reducing the peak stresses and redistributing the load to the surrounding tissue. This paper presents the effect of the structural integrity of the shape and stresses distribution on the global material behaviour of articular cartilage. Then modulus degradation appears to be a result of trabecular fracture rather than as a result of tissue level material degradation. Furthermore, we found that Young's modulus normal to the contact surface increases from the superficial to the deep zone in articular cartilage. © World Scientific Publishing Company.